Relevance of Diasporic Literature in the Globalised World: A Study - Kumar, Avinash (Integrated Journal for Research in Arts and Humanities, 2022)
Today science and technology have shrunk the whole world into a small and assessable global village. In this era of cutthroat competition, people readily avail the opportunity to move to any corner of the world to support themselves, affecting the world's cultural, political, social, economic and literary trends and issues. One academic issue worth analysing is diasporic literature and its relevance to the globalised world. This paper is motivated by a need to understand the relevance of Diaspora literature in the globalised world. It discusses different dynamics of Diasporic literature, its in-depth analysis, the literary tendencies and practices being observed, diversity of ethnicities, languages and religious traditions, etymological growth, issues of migration, the feelings, problems, solace and the acculturation of the migrating community, hybridity and its effects on the second generation in the aftermath of globalisation. I also intend to speculate on the fleeting notion of quality and how that relates to and affects the globe of our time.